The role of Legionella pneumophila serogroup 1 lipopolysaccharide in host-pathogen interaction - Palusińska-Szysz, Marta; Petzold, Markus (Frontiers in microbiology, 2019)
The L. pneumophila TF3/1 mutant of the Corby strain, which possesses a point mutation in the active site of the O-acetyltransferase, synthesized the polysaccharide chain with a reduced degree of substitution with O-acetyl groups. The mutant did not produce a high-molecular-weight lipopolysaccharide (LPS) fraction above 12 kDa. (Q3, R3). The disturbances in LPS synthesis have an effect on the composition of other macromolecules (lipids and proteins), as indicated by differences in the infrared absorption spectra between the L. pneumophila Corby strain and its TF3/1 mutant. The wild-type strain contained less N+-CH3 and C-N groups as well as more CH3 groups than the mutant. The fatty acid composition showed that the wild type strain synthesized more branched acyl residues (a15:0, i16:0, and a17:0), a less unsaturated acid (16:1), and a straight-chain acid (18:0) than the mutant. The mutant synthesized approximately twice more a long-chain fatty acid (20:0) than the wild type. The main differences in the phospholipids between both strains were found in the classes of phosphatidylcholines and phosphatidylglycerols. Substantial differences in the cell surface topography of these bacteria and their nanomechanical properties were shown by atomic force microscopy. The wild type strain had no undulated surface and produced numerous vesicles. In the case of the mutant type, the vesicles were not numerous, but there were grooves on the cell surface. The average roughness of the cell surface of the mutant was approximately two-fold higher than in the wild-type strain. In turn, the wild-type strain exhibited much better adhesive properties than the mutant. The kinetic study of the interaction between the L. pneumophila strains and Acanthamoeba castellanii monitored by Förster resonance energy transfer revealed a pronounced difference, i.e. almost instantaneous and highly efficient binding of the L. pneumophila Corby strain to the amoeba surface, followed by penetration into the amoeba cells. This process was clearly not as efficient in the case of the mutant. The results point to LPS and, in particular, to the length of the polysaccharide fraction as an important L. pneumophila determinant involved in the process of adhesion to the host cell.